2022
DOI: 10.1371/journal.pone.0269789
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pesticide use and pesticide residues in vegetables from two provinces in Central Vietnam

Abstract: Pesticide residue in food, especially in vegetables, is one of the important parameters to assess food safety. This study evaluates the pesticide use in vegetables from two provinces in Central Vietnamand and present data on pesticides detected in vegetables sampled from the sites. The potential health risk associated with the contamination of four commonly used pesticides in different vegetables is also discussed. Both household surveys and monitoring campaigns were conducted. The survey showed that improper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…In this study, no differences were observed regarding age, educational status, pregnancy count, history of miscarriages, dietary habits, and pre-consumption washing and cleaning habits of raw vegetables and fruits. The rate of applying any cleaning treatment before consuming raw fruits and vegetables was significantly higher in the women who had normal births [47]. Residues in agricultural products should be below permissible limits.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, no differences were observed regarding age, educational status, pregnancy count, history of miscarriages, dietary habits, and pre-consumption washing and cleaning habits of raw vegetables and fruits. The rate of applying any cleaning treatment before consuming raw fruits and vegetables was significantly higher in the women who had normal births [47]. Residues in agricultural products should be below permissible limits.…”
Section: Discussionmentioning
confidence: 96%
“…Te samples were collected during the rainy season in late August 2021. It is worth mentioning that pesticide contamination is considerably higher during the wet season compared to the dry season [14]. As described by the authors, this is due to the fact that pesticides from various sources can be washed into existing ones, leading to increased contamination levels.…”
Section: Study Design and Periodmentioning
confidence: 95%
“…Mặt khác, canh tác an toàn đóng vai trò quan trọng trong định hướng phát triển nền nông nghiệp (Bộ Nông nghiệp và Phát triển Nông thôn, 2016). Tuy nhiên, để đạt được năng suất và lợi nhuận, trong canh tác nông nghiệp, người nông dân sử dụng thuốc bảo vệ thực vật và phân bón hóa học, thuốc kích thích sinh trưởng cây trồng với liều lượng và tần suất cao hơn khuyến cáo; do đó, dẫn đến nông sản mang dư lượng thuốc bảo vệ thực vật, phân bón và các chất độc hại khác, gây ảnh hưởng trực tiếp hoặc gián tiếp đến sức khoẻ người nông dân và người tiêu dùng (Chau et al, 2022;El-Sheikh et al, 2022;Dinede et al, 2023). Bên cạnh đó, việc lạm dụng hóa chất nông nghiệp trong canh tác cây trồng cũng làm cho đất trồng ngày càng suy thoái, nghèo dinh dưỡng, các chất độc hại tích lũy vào đất ngày càng nhiều (Châu và ctv., 2019).…”
Section: Giới Thiệuunclassified